Variations in attack patterns between female and male opposite players in top-level volleyball - Sotiropoulos, K.; Drikos, S.; Barzouka, K. (International Journal of Sports Science & Coaching, 2022)
In volleyball, the opposite player is the most requested hitter since she/he is the player with a higher probability of successfully carrying out attacks. The main objective of this study was to analyze variables that predicted attack effectiveness, in top-level teams depending on gender. Inferential analysis and multinomial logistic regression were applied to analyze 1512 attacks of men and women opposite players from 79 sets of the six top-ranked teams in the Men and Women 2018 World Championships. The analysis revealed that in female volleyball to increase the odds for a winning attack from the opposite player, teams have to pass the ball more accurately, setters have to set in a faster tempo and opposites avoid off-speed attack and spike in a diagonal direction from position 2. On the contrary, in male volleyball the odds for a winning attack from the opposite player are increased when male setters set accurate to the pre-agreement point on the net independent of the quality of the previous pass, opposite players hit in parallel and volleyball coaches select proper line-up and process tactical substitutions to increase the number of rotations with an opposite player in the offensive zone.